Response to DNA damage: why do we need to focus on protein phosphatases? - Shimada, Midori; Nakanishi, Makoto (Frontiers in Oncology, 2013)
Eukaryotic cells are continuously threatened by unavoidable errors during normal DNA replication or various sources of genotoxic stresses that cause DNA damage or stalled replication. To maintain genomic integrity, cells have developed a coordinated signaling network, known as the DNA damage response (DDR). Following DNA damage, sensor molecules detect the presence of DNA damage and transmit signals to downstream transducer molecules. This in turn conveys the signals to numerous effectors, which initiate a large number of specific biological responses, including transient cell cycle arrest mediated by checkpoints, DNA repair, and apoptosis. It is recently becoming clear that dephosphorylation events are involved in keeping DDR factors inactive during normal cell growth. Moreover, dephosphorylation is required to shut off checkpoint arrest following DNA damage and has been implicated in the activation of the DDR. Spatial and temporal regulation of phosphorylation events is essential for the DDR, and fine-tuning of phosphorylation is partly mediated by protein phosphatases. While the role of kinases in the DDR has been well documented, the complex roles of protein dephosphorylation have only recently begun to be investigated. Therefore, it is important to focus on the role of phosphatases and to determine how their activity is regulated upon DNA damage. In this work, we summarize current knowledge on the involvement of serine/threonine phosphatases, especially the protein phosphatase 1, protein phosphatase 2A, and protein phosphatase Mg2+/Mn2+-dependent families, in the DDR.